Novel synergistic in situ synthesis of lithium-ion poly(ethylene citrate)-TiO2 nanocomposites as promising fluorine-free solid polymer electrolytes for lithium batteries. (December 2019) - Pignanelli, Fernando; Romero, Mariano; Castiglioni, Jorge; Faccio, Ricardo; Mombrú, Alvaro W.
Abstract: Here, we report a synergistic in situ synthesis of lithium-ion poly (ethylene citrate) with embedded titania nanoparticles in which the esterification process itself triggered the hydrolysis of the titanium alkoxide precursor to form a promising fluorine-free lithium-ion solid polymer electrolyte. Structural characterization by means of X-ray diffraction, small angle X-ray scattering and also confocal Raman spectroscopy revealed the formation of the polyester with embedded titania nanoparticles in agreement with our Raman spectra simulation by means of DFT methodologies. Our theoretical modeling of the polyester also envisaged the interaction of lithium-ion via a tridentate coordination with oxygen atoms of carboxylate (–COO - ) and ester (–COO–) groups. There is a slight increase in the degree of polymerization and thermal stability for our lithium-ion polyester with increasing titania nanoparticles concentration. In consequence, a two-order magnitude increase in the ionic conductivity was observed, yielding 1.74× 10 −4  S cm −1 for a 20% weight fraction of titania nanoparticles. Thus, involving a novel approach based in the synergistic in situ preparation of lithium-ion poly (ethylene citrate) with titania nanoparticles, this procedure contributes to solve the many safety and environmental issues of the constitutive materials of lithium-ion solid polymer electrolytes. Highlights: Esterification trigger hydrolysis of titanium alkoxide precursor to form nanocomposite. Experimental and theoretical insights on the structure of lithium-ion nanocomposite. Two-order magnitude increase of ionic conductivity with titania nanoparticle fillers.